2009
DOI: 10.1016/s1474-4422(09)70085-7
|View full text |Cite
|
Sign up to set email alerts
|

NORdic trial of oral Methylprednisolone as add-on therapy to Interferon beta-1a for treatment of relapsing-remitting Multiple Sclerosis (NORMIMS study): a randomised, placebo-controlled trial

Abstract: SummaryBackground Treatment of relapsing-remitting multiple sclerosis with interferon beta is only partly effective, and new more effective and safe strategies are needed. Our aim was to assess the efficacy of oral methylprednisolone as an add-on therapy to subcutaneous interferon beta-1a to reduce the yearly relapse rate in patients with relapsing-remitting multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 47 publications
1
46
1
1
Order By: Relevance
“…The steroid/IFN group had a lower relapse rate than the placebo group. The NORMINS study enrolled subjects on IFNB-1a SC TIW who had at least 1 relapse in the previous year to receive oral methylprednisolone 200 mg or placebo daily for 5 days every four weeks for 96 weeks [55].The primary outcome was mean yearly relapse rate which was significantly better in the steroid group. The study results are confounded by a high dropout rate and a loss of power due to slow recruitment.…”
Section: Combination Trialsmentioning
confidence: 99%
“…The steroid/IFN group had a lower relapse rate than the placebo group. The NORMINS study enrolled subjects on IFNB-1a SC TIW who had at least 1 relapse in the previous year to receive oral methylprednisolone 200 mg or placebo daily for 5 days every four weeks for 96 weeks [55].The primary outcome was mean yearly relapse rate which was significantly better in the steroid group. The study results are confounded by a high dropout rate and a loss of power due to slow recruitment.…”
Section: Combination Trialsmentioning
confidence: 99%
“…For example, a 3-year study by Ravnborg and colleagues in patients with relapsing-remitting MS (n = 341) found that the combination of methylprednisolone (500 mg orally in monthly 'pulses'; three doses over 3 days) and IFNβ-1a reduced the rate of relapses by 38% compared with IFN plus placebo, and patients in the combination arm also had improved MSFC metrics and MRI outcomes [Ravnborg et al 2010]. Thus monthly steroids remain in the list of options for second-line treatment for MS. Pulse steroids as an add-on to the first-line DMT is arguably the only combination therapy which is practically used for MS management today [Sorensen et al 2009;Kutz, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, periodic or monthly administration of systemic corticosteroids, such as intravenous methylprednisolone (IVMP) pulse therapy, was one of the first strategies for management of worsening or breakthrough MS and is still employed to enhance the effects of DMTs for MS [Myhr and Mellgren, 2009;Sorensen et al 2009;Lienert et al 2013;Zivadinov et al 2008Zivadinov et al , 2012Piri Cinar et al 2013;Mezei et al 2013;Shaygannejad et al 2013]. This approach developed after systemic corticosteroids were approved for MS relapse treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available data support an association between corticosteroid treatment and mood disorders as well as other neuropsychiatric disorders such as sleep disturbances, cognitive impairment, and psychosis in some patients [Iacovides and Andreoulakis, 2011;Klein, 1992;Lewis and Smith, 1983;Lienert et al 2013;Martinelli et al 2009;Paparrigopoulos et al 2010;Sellebjerg et al 1998;Sorensen et al 2009;Tsang and Macdonell 2011;Warrington and Bostwick, 2006]. Commonly occurring nonpsychiatric AEs for corticotropin injection are similar to those of corticosteroids, as related to stimulation of cortisol release, and include fluid retention and edema, possible change in glucose tolerance, elevated blood pressure, and increased appetite and weight gain.…”
Section: Introductionmentioning
confidence: 91%